The effects of subgrade clay condition on the structural behaviour of road pavements - Dawson, A. R. (1996)
This study examines deflections of a pavement under construction and the effects on it of the deformability of clays for different soil-water conditions. This analysis is based on a simple layered elastic analysis using a stress-strain model applicable for saturated and unsaturated conditions, established from the results of repeated load triaxial testing. Analysis of data from repeated load triaxial tests carried out on recompacted soils has enabled a new model to be developed. A simple plasticity-related version is presented for routine use.